Double-layer PAA with different pore sizes and its growth kinetics based on anodizing current curves - Pengze Li; Liyang Qin; Bowen Li; Yijing Tang; Lianyu Chen; Ye Song; Xufei Zhu (Scientific Reports)
Abstract The relationship between porous morphology and current-time curves cannot be explained by the field-assisted dissolution theory (FADT). Double-layer structures of porous anodic alumina (PAA) with different pore sizes were obtained by multi-step anodizations. These important results cannot be interpreted by the traditional FADT theory. Here, based on the theories of ionic current and electronic current, the always controversial growth kinetics of PAA are clarified by the current-time curves. The ionic current under high electric field is the driving force for the rapid growth of oxides, resulting in the decline of the current curve. The electronic current results in the rise of the current curve, and causes oxygen bubble to form the pore embryos. After the electrolyte enters the pore bottom, the thickness of the bottom barrier layer remains unchanged. Therefore, constant electronic current maintains the oxygen evolution and oxygen bubble mold. Constant ionic current maintains the oxide growth around the oxygen bubble mold at the pore bottom, and maintains the upward growth of PAA channel in the viscous flow mode. The field-assisted dissolution rate is much less than the rate of channel growth determined by the total current.